Language Philosophy and Changes in Meaning in Digital Culture : Language Philosophy and Changes in Meaning in Digital Culture - Reni Lumban Gaol; Hetty Zaharani (English Lecturers and Teachers Association (ELTA), 2026)
This study explores how digital culture affects changes in language meaning among junior high school students at SMP Yabes School in North Sumatra. Digital platforms such as WhatsApp, Instagram, and TikTok influence how students communicate, interpret, and construct meaning. Using a qualitative sociolinguistic approach, the study analyzed online discourse, social media interactions, and interviews with 25 students. Results reveal that students frequently adapt words, create hybrid code forms, and use emojis to express nuanced meanings. Philosophical insights on meaning, truth, and context provide a framework to understand these changes. The findings highlight the relevance of integrating philosophy of language and digital literacy in junior high education. In conclusion, this study emphasizes the need to incorporate digital literacy and the philosophy of language into junior high school curricula to better understand and adapt to the evolving language practices shaped by digital culture. Keywords : Philosophy of Language, Digital Culture, Meaning Change, Sociolinguistics